PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT MAYA MUNCAR CABANG SUNTER PODOMORO KOTA JAKARTA UTARA - Dhiba Labibah Ardeliana; Muhammad Gandung (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of Organizational Culture and Employee Work Motivation both partially and simultaneously at PT Maya Muncar, Sunter Podomoro branch, North Jakarta. This research method uses quantitative methods with a descriptive approach. The collection methods used are primary data and secondary data. The sampling technique in this study used the Saturated Sampling Technique of 60 respondents. The analysis techniques used are validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, determination coefficient test and hypothesis testing. Partial hypothesis testing of the Organizational Culture variable (X1) obtained the t value> t table (4.178> 2.002) and a significance value of 0.000 < 0.05. This means that Organizational Culture has a significant effect on Employee Performance (Y). Partial hypothesis testing of the Work Motivation variable (X2) obtained the value of t count> t table (4.178> 2.002) and a significance value of 0.001 < 0.05. This means that Work Motivation (X2) has a significant effect on Employee Performance (Y). Simultaneous hypothesis testing obtained fcount> ftabel (41.276> 3.156) and a significant value of 0.000 <0.05. So it can be concluded that Organizational Culture and Work Motivation simultaneously have a significant effect on Employee Performance (Y). Determination obtained Adjusted R Square of 0.577, meaning that the Organizational Culture and Work Motivation variables together have an influence contribution of 57,7% to Employee Performance. While the remaining 42,3% is influenced by other factors not examined in this study.